Osteopontin contributes to virus resistance associated with type I IFN expression, activation of downstream ifn-inducible effector genes, and CCR2+CD115+CD206+ macrophage infiltration following ocular HSV-1 infection of mice - Filiberti, Adrian; Gmyrek, Grzegorz B.; Berube, Amanda N.; Carr, Daniel J. J. (Frontiers in Immunology, 2023)
Ocular pathology is often associated with acute herpes simplex virus (HSV)-1 infection of the cornea in mice. The present study was undertaken to determine the role of early T lymphocyte activation 1 protein or osteopontin (OPN) in corneal inflammation and host resistance to ocular HSV-1 infection. C57BL/6 wild type (WT) and osteopontin deficient (OPN KO) mice infected in the cornea with HSV-1 were evaluated for susceptibility to infection and cornea pathology. OPN KO mice were found to possess significantly more infectious virus in the cornea at day 3 and day 7 post infection compared to infected WT mice. Coupled with these findings, HSV-1-infected OPN KO mouse corneas were found to express less interferon (IFN)-α1, double-stranded RNA-dependent protein kinase, and RNase L compared to infected WT animals early post infection that likely contributed to decreased resistance. Notably, OPN KO mice displayed significantly less corneal opacity and neovascularization compared to WT mice that paralleled a decrease in expression of vascular endothelial growth factor (VEGF) A within 12 hr post infection in the OPN KO mice. The change in corneal pathology of the OPN KO mice aligned with a decrease in total leukocyte infiltration into the cornea and specifically, in neutrophils at day 3 post infection and in macrophage subpopulations including CCR2+CD115+CD206+ and CD115+CD183+CD206+ -expressing cells. The infiltration of CD4+ and CD8+ T cells into the cornea was unaltered comparing infected WT to OPN KO mice. Likewise, there was no difference in the total number of HSV-1-specific CD4+ or CD8+ T cells found in the draining lymph node with both sets functionally competent in response to virus antigen comparing WT to OPN KO mice. Collectively, these results demonstrate OPN deficiency directly influences the host innate immune response to ocular HSV-1 infection reducing some aspects of inflammation but at a cost with an increase in local HSV-1 replication.